Financial Technology Application Success in the 4.0 Era - Riantama, I Gede Ega; Suardhika, I Nengah; Yuesti, Anik (International Journal of Psychosocial Rehabilitation, 2020)
The presence of the industrial era 4.0 has changed the way of life and way of life of the community at this time. One that is experiencing growth is financial transactions that are shifting towards application-based digital namely the application of Financial Technology applications. But from the success of the application, there are still problems that harm the user and indicate reducing the level of user confidence in the application. This study aims to analyze, test and explain the role of moderation of trust in the effects of system quality, information quality, service quality on application user satisfaction. The results show that information quality most determines user satisfaction. Meanwhile, the quality of service is not able to increase user satisfaction, but with the trust can strengthen the quality of application services in determining the satisfaction of application users, besides that the service is always available and on time when users experience problems that are needed by application users. This finding can enrich the success model of DeLone and McLean (2003) information systems that use system quality, information quality, and service quality variables to user satisfaction, in this study adding moderation variables, namely trust.